PENGARUH TINGKAT KEHADIRAN MAHASISWA TERHADAP HASIL BELAJAR KALKULUS MAHASISWA STIKOM TUNAS BANGSA - Ika Okta Kirana (JURNAL MATHEMATIC PAEDAGOGIC, 2020)
AbstractThe purpose of this research was to determine the relationship and influence of student attendance rates on student calculus learning outcomes at STIKOM Tunas Bangsa Pematangsiantar. This type of research is quantitative research. The sampling technique in this research used a judgmental sampling technique. The sample in this research was the first semester students majoring in Information Engineering class 19T01, amounting to 46 students. In collecting data used instrument documentation and questionnaires. To find out the influence of it is used simple regression analysis. Regression analysis results obtained significance value < 0.05 i.e. 0,000 <0.05 it means that there is a significant influence on the level of student attendance on calculus learning outcomes. Whereas for the linearity test, the significance value of deviation from linearity > 0.05 or 0.578 <0.05, which means that the data is linear patterned, with the regression formula is Y = 2.779 + 0.690X.Keywords: attendance rate, learning outcome